Build Your Own CNC Machine - Hood-Daniel, Patrick (Apress, 2012)
Your very own CNC Machine. Don’t think it’s an unrealistic dream. You’re holding in your hands the instruction manual for building your very own, fully functional, easy-to-maintain, and (relatively) inexpensive CNC machine. But we understand your disbelief — we’ve been there. Traditionally, for hobbyists, woodworkers, and anyone interested in do-it-yourself projects, the reality of owning a CNC machine has been far-fetched. Traditional CNC machines are expensive, complicated, and typically only found in large manufacturing companies that can afford them… because, well, did we mention that they are expensive? (Small hobbyist CNC machines can run anywhere from $7000 and higher; professional machines can cost millions of dollars!) But no more. For a fraction of the cost (how does under $800 sound?) of a commerciallyavailable CNC machine, you, too, can own one of these wonderful devices. You can cut, drill, mill, and carve to your heart’s content. You can create those things that sit currently in your imagination. But there’s a catch, obviously. The catch is you’ll have to build it yourself. But before you go shaking your head and muttering about how you don’t have the right tools for the job or the woodworking knowledge to get it done, just take a deep breath and pause. You can do this because every step of the process is covered in this book. A website has been created with videos, full color photos, and a discussion forum where you can post questions and get answers. Others have built this machine with a minimal number of tools and a complete lack of CNC machine experience — if they can do it, you can do it. The secret is taking your time, breaking up the project into small steps (which has been done for you with small, easy to read chapters), and knowing that help is just a website away.